Pengembangan Lembar Kerja Siswa (LKS) Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Penalaran Matematika - Sri Handayani; Novianti Mandasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to produce a valid and practical Problem Based Learning (PBL) based student worksheet for junior high school students in Lubuklinggau. This research is a development research or development research type formative research. The subjects of the study were 75 State Junior High School students in Lubulinggau City, 27 people from SMP N 9 Lubuklinggau, 27 people from SMP N 11 Lubuklinggau, and 21 people from SMP PGRI Lubuklinggau. Data collection techniques used are walk through, to determine the validity of student worksheets in content, construct and language as well as documents to determine the practicality of student worksheets. This research produces Problem Based Learning based student worksheets that can measure students' mathematical reasoning abilities. Overall test results with an average value of 70,15 mathematical reasoning ability stated good. Conclusions, Student Worksheets developed are valid and practical to use and have a potential effect on improving students' mathematical reasoning abilities. Keywords: Mathematical Reasoning Ability, LKS, Problem Based Learning.